2007
DOI: 10.21061/jcte.v23i1.446
|View full text |Cite
|
Sign up to set email alerts
|

A National Assessment of Perceived Instructional Needs For Professional Development of Part-Time Technical and Occupational Education Faculty in the Community Colleges in The U.S.

Abstract: The purpose of this study was to identify the perceptions of occupational education officers concerning the instructional skills professional development needs for part-time faculty members within the community colleges in the U.S. The types of instructional help part-time faculty members were perceived to need most were concentrated in the following areas: (a) identifying the learning characteristics of students; (b) alternating teaching methods to accommodate different learning styles; (c) participation in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…One of the most important skills that a faculty should have acquired, practiced, and developed regularly in her/his classroom is employing diverse types of teaching methods (Biggs & Tang, 2011). It is found that contingent faculty exercise few instructional pedagogies and lack the ability to incorporate new ones in their classroom (Christensen, 2008;Eagan, 2007;Kezar & Sam, 2010;Lei, 2007;Morthland, 2010;Sandford, Belcher, & Frisbee, 2007;Umbach, 2007). Lei (2007) concludes that part-time faculty members utilize traditional teaching styles when delivering instructions to students.…”
Section: Instructional Practicesmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most important skills that a faculty should have acquired, practiced, and developed regularly in her/his classroom is employing diverse types of teaching methods (Biggs & Tang, 2011). It is found that contingent faculty exercise few instructional pedagogies and lack the ability to incorporate new ones in their classroom (Christensen, 2008;Eagan, 2007;Kezar & Sam, 2010;Lei, 2007;Morthland, 2010;Sandford, Belcher, & Frisbee, 2007;Umbach, 2007). Lei (2007) concludes that part-time faculty members utilize traditional teaching styles when delivering instructions to students.…”
Section: Instructional Practicesmentioning
confidence: 99%
“…These findings have been reported by other scholars who reviewed a great number of studies in order to understand the instructional practices of adjunct faculty. For example, Sandford et al (2007) states that the most dominant teaching method used by part-time faculty is lecturing. Sandford et al (2007) add that the implementation of media, such as online discussion, distance learning, and other web-based activities, is hardly found in the part-timers' instructional practices.…”
Section: Instructional Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout educational professional devel--tors regarding incorporating newer strategies to developing lesson plans and to address a variety of learning styles while teaching (Sandford, Belcher, & Frisbee, 2014). Gone are the days of purely traditional lectures in education as today's students have become increasingly socially connected in nearly every aspect of their lives, including through online learning (Hannon, Riddle, & Ryberg, 2014) and use of social media (Yadav, 2015).…”
mentioning
confidence: 99%